Chemical Control of Margarodes prieskaensis (Jakubski) ( Coccoidea: Margarodidae) on Grape-vines - de Klerk, C.A. (South African Journal of Enology and Viticulture, 2017)
Hexachlorobutadiene was applied with hand soil - injector guns as well as on commercial scale in two established vineyards at a rate of 12 ml/m2 to control Margarodes prieskaensis (Jakubski). Adult females as well as male pre-pupae and pupae were effectively controlled. Best results were obtained with an application after harvest during March. Although the cyst stage was not affected, applications during two consecutive years could effectively control the pest. Dichloropropene, aldicarb, fenamiphos, carbofuran and oxamyl were found to be ineffective in the control of M. prieskaensis.